1988
DOI: 10.1152/ajpgi.1988.255.1.g85
|View full text |Cite
|
Sign up to set email alerts
|

Transport of guanidine in rabbit intestinal brush-border membrane vesicles

Abstract: The characteristics of guanidine uptake were studied in brush-border membrane vesicles isolated from the rabbit proximal intestine. Guanidine uptake was manyfold greater in the presence of an outward-directed H+ gradient (intracellular pH = 5.5; extracellular pH = 7.2) than in the absence of a H+ gradient (intracellular and extracellular pH = 7.2). The time course of guanidine uptake exhibited an overshoot phenomenon in the presence of the H+ gradient, indicating occurrence of uphill transport. This H+ gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
3
13
1
Order By: Relevance
“…A similar process has also been found in BBMV from small intestine [64] and placenta [65], neither of which display TEA/H+ exchange activity. The role of this process in the renal handling of OCs is not clear, although it does display a modest inhibitory interaction with several polyamines [64],…”
Section: Guanidine Transportsupporting
confidence: 72%
“…A similar process has also been found in BBMV from small intestine [64] and placenta [65], neither of which display TEA/H+ exchange activity. The role of this process in the renal handling of OCs is not clear, although it does display a modest inhibitory interaction with several polyamines [64],…”
Section: Guanidine Transportsupporting
confidence: 72%
“…76) The data showed that an outward H + gradient serves as the driving force for procainamide uptake by intestinal brush-border membrane vesicles. This H + gradient-dependent transport system speciˆcal-ly recognizes tertiary amines and is diŠerent from previously characterized H + W guanidine antiport system 77) and H + W thiamine antiport system. 78) Taken together, theseˆndings clearly indicate that organic cations with N, N-dimethyl or N, N-diethyl moieties such as diphenhydramine and procainamide are transported by a novel H + W tertiary amine antiport system in the intestinal brush-border membrane.…”
Section: Introductionmentioning
confidence: 54%
“…However, despite the evidence supporting an OC/H ϩ exchanger mode of activity for OCTN1, it is not clear that this cloned transporter is the process that dominates transport activity as measured in isolated renal luminal membranes. OC/H ϩ exchange activity as functionally expressed in renal cells, or more specifically, mediated exchange of TEA for H ϩ , appears to be restricted to the kidney and the liver (299); it is not found in the placenta or intestine, although both of these organs do express a transporter that mediates exchange of guanidine for H ϩ (121,289). OCTN1, however, is expressed in many tissues, including the placenta and intestine (538).…”
Section: S[t/s]ivte[w/f][d/ N]lvcmentioning
confidence: 99%